1988
DOI: 10.1002/j.1460-2075.1988.tb03132.x
|View full text |Cite
|
Sign up to set email alerts
|

A molecular map of the chicken major histocompatibility complex: the class II beta genes are closely linked to the class I genes and the nucleolar organizer.

Abstract: A molecular map of the chicken major histocompatibility complex: the class 11 genes are closely linked to the class I genes and the nucleolar organizer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
3

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(144 citation statements)
references
References 50 publications
3
138
3
Order By: Relevance
“…At the start of this work, it had been reported that there were four classical class I genes in the chicken MHC (B12 haplotype), but studies of two haplotypes (B12 and B19) had reported cDNA clones for only one gene (2,15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the start of this work, it had been reported that there were four classical class I genes in the chicken MHC (B12 haplotype), but studies of two haplotypes (B12 and B19) had reported cDNA clones for only one gene (2,15).…”
Section: Resultsmentioning
confidence: 99%
“…chicken MHC is simpler and smaller, with the genes arranged differently (1)(2)(3)(4)(5). Moreover, the chicken MHC can determine decisive resistance and susceptibility to several infectious pathogens, as well as response to both live and killed commercial vaccines (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…HA has the advantage of speed and ease. Besides the MHC complex, chickens also have an Rfp-Y-system (Guillemot et al, 1988;Miller et al, 1994). However, identi¢cation of Rfp-Y (MHC-like) haplotypes seems of minor importance (Pharr et al, 1996(Pharr et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Among the genetic loci potentially involved in the immune response, the chicken MHC can determine decisive resistance and susceptibility to several infectious pathogens, as well as the response to both live and killed commercial vaccines (1)(2)(3)(4). Compared with typical mammals such as humans and mice, the chicken MHC is simpler, smaller, and rearranged (5)(6)(7)(8). Based on these data, we developed the concept of a "minimal essential MHC" to give a molecular basis to the striking functional properties of the chicken MHC (7)(8)(9).…”
mentioning
confidence: 99%